IMPROVING ENGLISH VOCABULARY MASTERY THROUGH RIDDLES GAME TO THE FIFTH STUDENTS OF SD XAVERIUS 9 PALEMBANG - Tarima Parapat; Gaya Tridinanti; Nita Ria (Universitas Tridinanti Palembang, 2022)
Vocabulary is central to learning of foreign language at primary level. Every person need vocabulary to express their ideas especially in English, even in a simple of conversation. The purpose of this study was to find out whether or not there was any significant difference in English Vocabulary to between the fifth students of SD Xaverius 9 Palembang who were taught by using Riddles Game and those who were not. The method in this study was quantitative research with quasi-experimental for control group and experimental group. The sample of this study was fifty seven students of the fifth grade of SD Xaverius 9 Palembang in academic year 2018/2019. The data were analyzed by using independent sample ttest. The result of Independent Sample t-test showed that the value of t-obtained (6.540) > the value of t-table (1.673) with the significance value (0.00) was lower than the alpha value (0.05). It means that there was a significant difference in English vocabulary to the students of SD Xaverius 9 Palembang between who were taught by using Riddles game and those who were not.Keywords: vocabulary, Riddles game